2017
DOI: 10.1055/s-0037-1603332
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment Patterns for Lower Extremity Trauma in the United States: Flaps versus Amputation

Abstract: Background Treatment algorithms for large soft tissue defects in lower extremity trauma are not clearly defined. The aim of this study is to determine if there are geographic or demographic differences in the management of open tibia fractures with soft tissue defects requiring either soft tissue reconstruction or amputation in the United States (US). Methods A retrospective analysis was performed on the Nationwide Inpatient Sample (NIS), 2000 to 2011. We evaluated flap and amputation rates in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The treatment algorithm for traumatic lower extremity wounds is also poorly defined, with some studies suggesting that the question of free tissue transfer versus amputation in this population, is largely incumbent upon regional variability in practice, in urban versus rural hospital settings, with the former presumably more likely to have large academic facilities capable of free tissue transfer. 19 Studies originating out of our modern war experience have shown that healthy patients with an otherwise traumatized or painful extremity can in fact do better with an amputation. 20 This bears a critical distinction from the chronic wound patient: the former possesses physiologic reserve enough to entrain his or herself to an amputation.…”
Section: Chronic Versus Traumatic Lower Extremity Woundsmentioning
confidence: 99%
“…The treatment algorithm for traumatic lower extremity wounds is also poorly defined, with some studies suggesting that the question of free tissue transfer versus amputation in this population, is largely incumbent upon regional variability in practice, in urban versus rural hospital settings, with the former presumably more likely to have large academic facilities capable of free tissue transfer. 19 Studies originating out of our modern war experience have shown that healthy patients with an otherwise traumatized or painful extremity can in fact do better with an amputation. 20 This bears a critical distinction from the chronic wound patient: the former possesses physiologic reserve enough to entrain his or herself to an amputation.…”
Section: Chronic Versus Traumatic Lower Extremity Woundsmentioning
confidence: 99%
“…Treatment of critical-size bone defects and extensive soft tissue loss of the tibia in open fractures is a challenge because of the limited amount of soft tissue in the tibia, the subcutaneous location of the bone, its poor vascularity, and the high risk of infection [2] . The amputation rate for Gustilo grade IIIB/C open fractures can be as high as 26.8% [3] . The main purpose of open fracture treatment is to repair bone defects and perform soft tissue reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, primary treatment with amputation was strongly suggested, to avoid early complication such as infectionsandtissuenecrosispropagation,withasignificantlowering of life quality for patients. On the other hand, when salvage is the primary option, late bone infections, delayed bone union or non-union,venousinsufficiency,representadditionalpost-operativecriticismsthatseverelyaffecttherestorationoflimbstructure andfunction [3,4].…”
Section: Introductionmentioning
confidence: 99%